Емоційна регуляція діяльності людини - Самелюк, А. А.; Шашко, О. В. (ХНУРЕ, 2019)
The modern theoretical approaches to the problem of self-regulation as the adaptive potential of the individual are considered in the article. The analytical overview of current researches of the problems of self-regulation and analysis of emotional and volitional processes involved in the activities of adaptive mechanisms is presented